Specific and Non-Specific Safety Testing of Red Gedi Leaf Ethanol Extract (Abelmoschus manihot L. Medik) - Joni Tandi; Yuliet Susanto; Tien Wahyu Handayani; Magfirah Magfirah; Muthmainah Tuldjanah (Jurnal Jamu Indonesia, 2026)
Red gedi leaves (Abelmoschus manihot (L.) Medik) are traditionally used for their antidiabetic, antioxidant, and hepatoprotective properties. This study aimed to characterize the specific and non-specific quality parameters of red gedi leaf ethanol extract based on Herbal Pharmacopoeia standards. Extraction was performed by maceration using 96% ethanol, yielding 6.72%. Phytochemical screening confirmed the presence of flavonoids, saponins, tannins, quinones, and steroids, with a high total flavonoid content of 56.97 ± 3.75 mg/g. Non-specific parameters, including water content, drying loss, ash values, microbial contamination, and heavy metal levels (Pb and Cd), complied with the required standards. Organoleptic evaluation showed a viscous extract with brownish color, slightly astringent taste, and characteristic odor. These results indicate that red gedi leaf ethanol extract meets Herbal Pharmacopoeia quality requirements and has potential for development as a standardized antioxidant herbal product.